Mejoramiento genético y actividades relacionadas. Mejoramiento de características individuales. Resistencia a enfermedades virosas - International Center for Tropical Agriculture (International Center for Tropical Agriculture, 1987)
During 1986, research emphasis was shifted to BGMV while BCMV research focused on the incorporation of blackroot resistance in African germplasm and the backcrossing of I gene into Latin American var. The identification of alternate host plant species for BGMV is critical in the understanding of the endemic and epidemic characteristics of this virus. Using the artificial inoculation methodology implemented at CIAT, the evaluation of 57 plant species considered as possible BGMV hosts was initiated. To date, Phaseolus lunatus, P. coccineus, P. acutifolius, Canavalia sp., Vigna radiata, and Macroptilium lathyroides have been shown to be potential reservoirs of BGMV in nature. Preliminary isolation work conducted with the CIAT isolate of BGMV resulted in purified preparations of acceptable concn. Various bean chlorotic mottle virus isolates have been made and are currently being characterized. Results are included in table form. (CIAT)